Effects of trunk muscle activation on trunk stability, arm power, blood pressure and performance in wheelchair rugby players with a spinal cord injury. (4th July 2022) - Kouwijzer, Ingrid; van der Meer, Mathijs; Janssen, Thomas W.J.
Abstract : Objective: In wheelchair rugby (WR) athletes with tetraplegia, wheelchair performance may be impaired due to (partial) loss of innervation of upper extremity and trunk muscles, and low blood pressure (BP). The objective was to assess the effects of electrical stimulation (ES)-induced co-contraction of trunk muscles on trunk stability, arm force/power, BP, and WR performance. Design: Cross-sectional study. Setting: Rehabilitation research laboratory and WR court. Participants: Eleven WR athletes with tetraplegia. Interventions: ES was applied to the rectus abdominis, obliquus externus abdominis and erector spinae muscles. For every test, the ES condition was compared to the non-ES condition. Outcome measures: Stability was assessed with reaching tasks, arm force/power with an isokinetic test on a dynamometer, BP during an ES protocol and WR skill performance with the USA Wheelchair Rugby Skill Assessment. Results: Overall reaching distance (ES 14.6 ± 7.5 cm, non-ES 13.4 ± 8.2 cm), and BP showed a significant increase with ES. Arm force (ES 154 ± 106 N, non-ES 148 ± 102 N) and power (ES 37 ± 26 W, non-ES 36 ± 25 W), and WR skills were not significantly improved. Conclusion: ES-induced trunk muscle activation positively affects trunk stability and BP, but not arm force/power. No effects were found in WR skill performance, probably due to abdominal strapping. More research is needed to assess different ES (training) protocols and longitudinal effects.